The Effect Of Policy Interest Rate On Countries’ Inflation Rates And Economic Growth: Research On G-8 Countries - EKŞİ, İbrahim Halil; ŞİT, Ahmet; SALMAN, Ceren; dogan başar, berna (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
Aim of this study is to investigate the effects of countries' policy interest rates on inflation rates. The period of the study is 2000-2023 and the data were examined annually. The sample of the study consists of G-8 countries, which are considered the most developed countries in the world. The independent variable of the study is the policy interest rate, and the dependent variables are the inflation rate and economic growth rates of the countries. As a method, due to the cross-sectional dependency problem between the series, Westerlund (2010) cointegration test, AMG and CCE coefficient estimators are created from the second generation panel data techniques. As a result of the analysis, it is seen that the policy interest rate has an inverse effect for the G-8 countries, that is, as the policy interest rate increases, the inflation rate of the countries decreases. In Model, where economic growth is the dependent variable, it is seen that there is an inverse relationship between the policy interest rate and the economic growth rate, that is, as the policy interest rate increases, it has a negative effect on economic growth. This result is consistent with some studies in the literature and inverse with some studies. The reason for this can be stated as the increase in policy interest rates in countries, which increases the cost of foreign resources, while in businesses that operate mainly with foreign resources, a contraction in the markets may occur due to the increase in the cost of foreign resources.